Unintended consequences of technology in competency-based education: a qualitative study of lessons learned in an OtoHNS program - Mary Ott; Tavis Apramian; Sayra Cristancho; Kathryn Roth (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Formative feedback and entrustment ratings on assessments of entrustable professional activities (EPAs) are intended to support learner self-regulation and inform entrustment decisions in competency-based medical education. Technology platforms have been developed to facilitate these goals, but little is known about their effects on these new assessment practices. This study investigates how users interacted with an e-portfolio in an OtoHNS surgery program transitioning to a Canadian approach to competency-based assessment, Competence by Design. Methods We employed a sociomaterial perspective on technology and grounded theory methods of iterative data collection and analysis to study this OtoHNS program’s use of an e-portfolio for assessment purposes. All residents (n = 14) and competency committee members (n = 7) participated in the study; data included feedback in resident portfolios, observation of use of the e-portfolio in a competency committee meeting, and a focus group with residents to explore how they used the e-portfolio and visualize interfaces that would better meet their needs. Results Use of the e-portfolio to document, access, and interpret assessment data was problematic for both residents and faculty, but the residents faced more challenges. While faculty were slowed in making entrustment decisions, formative assessments were not actionable for residents. Workarounds to these barriers resulted in a “numbers game” residents played to acquire EPAs. Themes prioritized needs for searchable, contextual, visual, and mobile aspects of technology design to support use of assessment data for resident learning. Conclusion Best practices of technology design begin by understanding user needs. Insights from this study support recommendations for improved technology design centred on learner needs to provide OtoHNS residents a more formative experience of competency-based training. Graphical abstract